A novel model to predict phase equilibrium state of hydrates from the relationship of gas solubility - Jiang, Jianbing; Jiang, Jianxun; Mao, Jinchen; Li, Dong; Liu, Tuanhui; Pan, Zhong (Frontiers in Energy Research, 2024)
The study of phase equilibrium of hydrates is crucial, but scientists often focus on the chemical potential of hydrates and ignore gas solubility. With the development of microscopic research, scientists have gradually realized that gas solubility plays an important role in the formation of hydrates. However, there is little research on the relationship between the equilibrium state of hydrates and gas solubility, and this study fills this gap. In this work, a solubility model based on gas liquid equilibrium theory showed a higher prediction accuracy in comparison of PR equation and Duan model and then was used to calculate gas solubility under hydrate phase equilibrium state. Afterwards, according to the relationship between gas solubility and hydrate phase equilibrium temperature, a novel model was developed to predict hydrate equilibrium state based on gas solubility and further compared with Chen–Guo model and CSMGem in prediction accuracy under pure water and brine settings. The results showed: (a) The calculation deviation of the solubility model was 0.7~8.7% in pure water settings and 2.6~11.7% in brine settings; (b) A strong linear correlation between the phase equilibrium temperature of hydrates and the gas solubility was also found; (c) This proposed model achieved over 10 times the accuracy of the Chen–Guo model and the CSMGem in predicting the phase equilibrium state of N2 and CO2 hydrates, and 3-10 times higher accuracy than that of the Chen–Guo model and CSMGem in brine. This work suggests that the gas solubility equilibrium theory can provide a more accurate prediction of hydrate states.